Contributions of Public Health to nursing practice - Káren Mendes Jorge de Souza; Clarissa Terenzi Seixas; Helena Maria Scherlowski Leal David; Aline Queiroz da Costa
ABSTRACT Objective: Analyze the perceptions of undergraduate nursing students about the contributions of public health to nursing practice in the Unified Health System. Method: Qualitative Descriptive Study. Data collection was carried out through semi-directed interviews with 15 students. The language material was analyzed according to content and thematic analysis. Results: Thematic categories were established, namely: "Perceptions about Public Health" and "Contribution of Public Health to nursing practice in the Unified Health System". Final considerations: Perceptions about Public Health are diversified, but converge to the recognition of this field as the basis for training nurses qualified to work in the SUS with technical competence, autonomy and focusing on the integrality in health care.